Diabetic peripheral neuropathy in people with type 2 diabetes: too little too late. Issue 4 (18th December 2019) - Javed, S.; Hayat, T.; Menon, L.; Alam, U.; Malik, R. A.
Abstract: Diabetic peripheral neuropathy in people with type 2 diabetes is poorly managed because of its insidious onset, delayed diagnosis and more complex aetiology resulting from the contribution of not only hyperglycaemia, but also ageing, hyperlipidaemia, hypertension and obesity. Because there is no US Food and Drug Adminstration‐approved disease‐modifying therapy for diabetic peripheral neuropathy, the key to ameliorating it in type 2 diabetes has to be through earlier diagnosis and timely multi‐factorial risk factor reduction. The management of painful diabetic peripheral neuropathy also requires a detailed appraisal of the choice of therapy, taking into account efficacy, patient wishes, comorbidities, side effect profile and potential for abuse. What's new?: Neuropathy is a common and severe consequence of diabetes mellitus. Early diabetic neuropathy is difficult to diagnose. There are no disease‐modifying therapies for diabetic neuropathy. The diagnosis of diabetic neuropathy relies on clinical evaluation, which detects disease too late. More objective measures of diagnosing and assessing the severity of diabetic neuropathy are required. The diagnostic approach to diabetic neuropathy needs to change to identify early nerve damage, especially in type 2 diabetes. The management of diabetic neuropathy in type 2 diabetes requires a multifactorial approach and tailored pharmacotherapy.